ANALISIS PENGARUH KUALITAS LAYANAN WEBSITE TERHADAP LOYALITAS PELANGGAN E-COMMERCE BUKALAPAK - Dendy Kurniawan; Neilin Nikhlis (Elkom : Jurnal Elektronika dan Komputer, 2020)
E-commerce competition in Indonesia makes e-commerce companies compete to develop strategies to win the competition. Customer loyalty is an important factor to lead in the competition. This research focuses on how much influence website service quality has on customer loyalty. This research is also to find out which website quality factors have the most influence on customer loyalty with customer satisfaction as a mediating factor. The factors that influence e-commerce customer loyalty are analyzed using concepts including the dimensions of service quality consisting of (physical evidence, reliability, responsiveness, assurance, empathy) and Corporate Image as the variable that influences and Customer Satisfaction as the variable that is affected. The sample in this study were 96 respondents. With the sampling method using the purposive sampling method. The results obtained that there is a positive and significant influence between the dimensions of service quality and company image on customer satisfaction. Keywords: E-commerce website, Service Interaction Quality, Customer Satisfaction